Antifouling and permeability flux enhancement PVDF- PVP membrane using nano-titanium dioxide for Palm Oil Mill Effluent (POME) color removal - Che Man, Hasfalina; Md Yunos, Khairul Faezah; K. K., Katibi; M. U., Abba (Farm Machinery Industrial Research Corp., 2021)
The dark brownish color effluent from palm oil mill effluent (POME) has continued to receive considerable interest and posed widespread concern due to its repercussions on water bodies. This study examines the performance of hydrophilic composite hollow fibre poly (vinylidene fluoride) (PVDF)-polyvinylpyrrolidone(PVP) membrane embedded with titanium dioxide (TiO2) nanoparticles as a robust antifouling intermediary for the decolourization of palm oil mill effluent (POME). The nanocomposite hollow fibre membrane with varied TiO2- nanoparticles loadings (0-2.0 wt.%) were swirled through phase inversion procedure to provide a negatively charged surface. The developed nanocomposite membranes were analyzed and compared according to SEM, contact angle, EDX, permeability flux, COD and color removal, and fouling resistance from (POME). Color removal, fouling resistance, and flux permeability enhanced with a rise in TiO2 loading. The flux efficiency of the membranes was assessed using pure water and POME as a feed liquid. Results show that the membraneembedded with 1.0 wt% concentration of TiO2 exhibited higher performance showing pure water flux and POME flux, COD and color removal of 120.74 L/m2h, 74.3 L/m2h, 90.1%, and 94.7% from POME respectively. Furthermore, an excellent fouling hindrance was attained, thereby allowing the percentage of flux recovery ratio (FRR) recorded was 95.46%, 92.49%, and 87.49%, after three cycles of uninterrupted filtrations for a period of 540 min. Yet, declination in flux and fouling resistance was observed at supplemental loading of 1.5 and 2.0 wt%- TiO2 owing to the accumulation of nanofillers in the membrane matrix at the higher concentrations.